2015
DOI: 10.1111/avsc.12171
|View full text |Cite
|
Sign up to set email alerts
|

Fire effects on invasive and native warm‐season grass species in a North American grassland at a time of extreme drought

Abstract: Question: Can the timing of cutting or burning be used to selectively damage an invasive C 4 grass species while limiting collateral damage to dominant native C 4 grass species in a grassland community? Location: A medium to short grass prairie in central Texas, US.Methods: We conducted six cut and burn trials between June 2011 and January 2012 during an exceptional drought year. Target species were the native, perennial, C 4 grass Schizachyrium scoparium (little bluestem) and the introduced, perennial, C 4 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Havill et al. () address the issue of how to target invasive species without causing collateral damage to native species in the fire‐prone shortgrass prairies of central Texas, by comparing the impacts of different burning and cutting treatments on the response of an introduced grass and a native grass.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Havill et al. () address the issue of how to target invasive species without causing collateral damage to native species in the fire‐prone shortgrass prairies of central Texas, by comparing the impacts of different burning and cutting treatments on the response of an introduced grass and a native grass.…”
mentioning
confidence: 99%
“…In the recent study of Havill et al. () they took into account Pyke et al. 's () framework and focused on two C 4 perennial grasses, one introduced and the other native.…”
mentioning
confidence: 99%
“…There are not many applications of this approach, but a study by Havill et al. () showed that a nonnative C 4 grass species was more sensitive to burning during a drought than its native counterpart, supporting the notion that nonnative management should be poised for opportunities arising from a combination of disturbances, including extreme events.…”
Section: Discussionmentioning
confidence: 99%
“…), because native species are often competitively superior under resource limitation (e.g., lower water demands, Cavaleri and Sack , and lower sensitivity to burning, Havill et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous grassland studies do not show enhanced effects of burning during drought, but in those cases dry years occurred immediately before (Larios et al, ) or at the same time (Arterburn et al, ) as fire, rather than during post‐fire succession. Other work suggests that water availability after prescribed fire can alter succession, although the direction of effects on exotic grasses is inconsistent for reasons that remain unclear (Davy & Dykier, ; Havill, Schwinning, & Lyons, ; Kimball, Goulden, Suding, & Parker, ; Villarreal, Norman, Buckley, Wallace, & Coe, ). At least one manipulative, factorial experiment supports stronger effects of water availability than burning on annual grass biomass (Potts, Suding, Winston, Rocha, & Goulden, ).…”
Section: Discussionmentioning
confidence: 99%